Sinkritasi Ajaran Sesat dan Teori Konspirasi di Media Sosial Menurut Perspektif Pemikiran Islam: Synchronization of Deviant Teachings and Conspiracy Theories on Social Media according to the Perspective of Islamic Thought - Che Nordin, Mohd Khairul Naim (Jurnal Usuluddin, 2024)
The invention of the internet and the development of social media have enabled the rapid and widespread communication in every corner of the world. It gives an equal opportunity to everyone to express their ideas and views whether they are facts, false data and assumptions. The context and reality of the internet which provides unfiltered information and puts the onus on users to take responsibility for dealing with the overflow of information has opened up space for the spread of conspiracy theories, including those linked to religion. The potential of social media to attract followers has been exploited by some individuals and groups to spread deviant teachings in order to gain followers. To attract recognition, they incorporate conspiracy theories and eschatology into their teachings. By using the library research method through the analysis of related works, this paper examines the syncretism between conspiracy theories and deviant teachings in Malaysia through several websites and social media accounts. The study categorizes the characteristics that lead to the syncretization into four, namely epistemology, doctrine, worldview and social aspects.